Analysis of the Factors that Affect Financial Distress in Transportation Sector Companies Listed on the IDX for the Period 2018 – 2020 - Sitanggang, Tina Novianti; Sinaga, Ayu Stevani; Ritonga, Tuti; Pratiwi, Desy; Waruwu, Lismawati (Budapest International Research and Critics University, 2022)
The purpose of this research is to find out what factors influence the occurrence of bad financial conditions (Financial Distress) in a company. Transportation sector companies are the population in this study, with a sample of 33 companies with a three-year study period. The technique used in determining the sample is purposive sampling technique. The independent variables in this study: ROA, Current Ratio, Debt Ratio and Company Size. The dependent variable in this study: Financial Distress as measured using the modelZmijewski. The results showed thatROA partially has a significant negative effect on Financial Distress, Current Ratio partially has no significant effect on Financial Distress, Debt Ratio partially has a significant positive effect on Financial Distress, Company Size partially does not have a significant effect on Financial Distress and ROA, Current Ratio, Debt Ratio and Company Size simultaneously affect Financial Distress.